Oppenheimer and the atomic bomb - Singer, Eric, 1968-; Bird, Kai; Sherwin, Martin J. (G.P. Putnam's Sons, 2025)
"The #1 New York Times bestselling, Pulitzer Prize-winning book American Prometheus was the inspiration for the blockbuster film, OPPENHEIMER, and is now adapted for middle school readers"-- Provided by publisher.